High-investment HR values and firm performance among local firms and U.S. MNCs' subsidiaries in South Asia: a comparative study. Issue 13 (19th July 2016) - Colakoglu, Saba; Allen, Matt; Miah, Khasro; Bird, Allan
Abstract : Grounded in institutional theory, this study investigates the differential adoption and internalization of high-investment human resource (HR) values by local companies and by subsidiaries of US firms located throughout South Asia; and the impact of these HR values on firms' performance. In line with our predictions, results suggest that US subsidiaries have a greater rate of adoption of high-investment HR values compared to local South Asian firms. Contrary to our predictions, however, both types of firms are similar in the level of internalization of their respective HR values. Finally, while greater levels of high-investment HR value adoption is associated with firm performance across the board, this relationship tends to be stronger for US MNCs' subsidiaries compared to local South Asian companies. Theoretical and practical implications for the transfer and diffusion of high-investment HR values in institutionally and culturally distant contexts are discussed.